Kepala Madrasah dan Perannya dalam Meningkatkan Profesionalisme Guru: Studi Eksplorative di MTs Istiqamah Talu - Ismaiza Busti; Mahyudin Ritonga; Ahmad Lahmi (UMSU, 2021)
The Head of Madrasah has a role in various matters related to improving the quality of both human resources and infrastructure in each madrasah he leads, teachers as human resources elements in madrasahs need strategic steps taken by the head of madrasah to improve their professionalism, this research aims to explore how the role of madarasah head in improving teacher competence in MTs Istiqamah Talu Talamau Subdistrict. Research is designed with an explorative qualitative approach, namely a study that aims to find the role performed by the head of madrasah through the search of various sources, the source of this research is madrasah supervisors, teachers in MTs Istiqamah and madarasah heads as a form of confirmation, to obtain data from the specified sources, in this research used observation techniques, interviews, documentation studies and focus group discussions, data analysis used is descriptive qualitative. The result of the research is that the head of madrasah plays a role in increasing the professionalism of teachers in the form of informative, coordinate, consultative and informative.